Interpersonal Psychotherapy for Adolescents With Mood and Behavior Dysregulation: Evidence-Based Case Study. Issue 4 (1st October 2016) - Miller, Leslie; Hlastala, Stefanie A.; Mufson, Laura; Leibenluft, Ellen; Riddle, Mark
ABSTRACT: Interpersonal psychotherapy for depressed adolescents, an evidence-based psychotherapy, has been adapted for youth with chronic irritability and excessive reactivity (i.e., temper outbursts), to create Interpersonal Psychotherapy for Mood and Behavior Dysregulation (IPT-MBD). Youth with chronic irritability and excessive reactivity were originally conceptualized as severe mood dysregulation (SMD) and in the Diagnostic and Statistical Manual of Mental Disorders (5th ed.) as disruptive mood dysregulation disorder. Because outbursts are the most prominent symptom, behavioral management strategies are typically a common focus of treatment. These outbursts, along with other mood symptoms, result in significant impairment in multiple domains, with a particularly adverse impact on interpersonal functioning. For this reason improving relationships is an important target for treatment. We present an evidence-based case study of an adolescent who met research criteria for SMD and who received the IPT-MBD intervention as part of a research study. Monthly ratings assessing severity and improvement of SMD symptoms were conducted by an independent evaluator. This adolescent had an overall improvement in SMD symptoms, attended all scheduled therapy sessions, and parent and teen reported satisfaction with the treatment. We discuss factors that may influence the effectiveness of this treatment.